2013
DOI: 10.1016/j.jhealeco.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

On correcting the concentration index for binary variables

Abstract: This article discusses measurement of socioeconomic inequalities in the prevalence of a health condition, in response to the recent exchange between Guido Erreygers and Adam Wagstaff, in which they discuss the merits of their own corrections to the frequently used concentration index. We first reconcile their debate and discuss the value judgments implicit in their indices. Next, we provide a formal definition of the previously undefined value judgment in Wagstaff's correction. Finally, we show empirically tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
150
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(151 citation statements)
references
References 15 publications
0
150
0
1
Order By: Relevance
“…Interested readers may refer to Petrie and Tang (2008) (Wagstaff, 2009;Kjellsson and Gerdtham, 2013;Kjellsson et al, 2015;Petrie et al, 2015). Hereafter we refer to the standardized Gini as Giniw for Gini Wagstaff.…”
Section: -----------------------------------------mentioning
confidence: 99%
“…Interested readers may refer to Petrie and Tang (2008) (Wagstaff, 2009;Kjellsson and Gerdtham, 2013;Kjellsson et al, 2015;Petrie et al, 2015). Hereafter we refer to the standardized Gini as Giniw for Gini Wagstaff.…”
Section: -----------------------------------------mentioning
confidence: 99%
“…A potential problem may arise when the health variable is restricted [6][7][8][9][10]. While the concentration index for an unrestricted variable is asymptotically bounded in the (−1; 1) interval, this does not hold true for restricted health outcomes: Wagstaff [6] has shown that the bounds of the concentration index for binary health outcomes depend inversely on the mean.…”
Section: Correcting the Concentration Index For Restricted Health Varmentioning
confidence: 99%
“…Thus, comparing health inequalities between populations with rather different overall population health (e.g. the prevalence of a disease or the share of immunized infants) without accounting for the prevalence-dependency of the underlying inequality measure may lead to misleading results [6][7][8][9][10]. Moreover, the choice as to whether one measures health attainments or shortfalls may also have considerable impact on the results [9,10].…”
Section: Correcting the Concentration Index For Restricted Health Varmentioning
confidence: 99%
See 2 more Smart Citations